2022
DOI: 10.4265/bio.27.179
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Conditions for External Quality Control in Identification of Microorganisms using Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry

Abstract: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) was approved for medical use in 2011 and is currently used as a rapid, accurate and lowcost technique for bacterial identification. External quality control for medical analysis is monitored using tests of the Japanese Association of Medical Technologists and Prefectural Association of Clinical Laboratory Technologists and through user surveys of reagent and equipment manufacturers. However, external quality control of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…An external accuracy survey was conducted by the Japanese Association of Medical Technologists (JAMT) and prefectural associations of clinical laboratory technologists, and through user surveys of reagent equipment manufacturers. However, since external accuracy control of bacterial typing using MS is performed on a small scale, we also developed procedures for this process using MALDI-TOF MS (Sogawa et al, 2022) . In this report, we describe the results of these procedures for evaluation of external accuracy control of bacterial typing with MS at 228 sites, using the identification consistency rate (Score Value) .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…An external accuracy survey was conducted by the Japanese Association of Medical Technologists (JAMT) and prefectural associations of clinical laboratory technologists, and through user surveys of reagent equipment manufacturers. However, since external accuracy control of bacterial typing using MS is performed on a small scale, we also developed procedures for this process using MALDI-TOF MS (Sogawa et al, 2022) . In this report, we describe the results of these procedures for evaluation of external accuracy control of bacterial typing with MS at 228 sites, using the identification consistency rate (Score Value) .…”
mentioning
confidence: 99%
“…The Japan Hospital Association conducted a survey of internal accuracy control in 2017 and found that more than 90% of sites performed internal accuracy control of biochemical and hematology tests, but that only 54.8% controlled the internal accuracy of microbiology tests. In addition, more than 98.0% of sites performed external accuracy control of biochemical and hematology tests, whereas only 90.4% performed external accuracy control of microbiology tests (Sogawa et al, 2022) .…”
mentioning
confidence: 99%
See 1 more Smart Citation